Merawat Keberagaman di Kota Medan: Konstruksi Relasi Agama dan Budaya Lokal - Paisal Siregar; Katimin Katimin; Wirman Wirman (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
Indonesia is widely recognized as a multicultural society in which religious and cultural diversity shapes everyday social relations. Medan City, a major urban center in North Sumatra, provides a concrete context for examining how diversity is nurtured and maintained through local cultural practices. This article analyzes the construction of relations between religion and local culture in Medan, focusing on how these relations contribute to social harmony in a plural urban setting. The study employs a qualitative descriptive-analytical method based on literature review, policy documents, and relevant previous studies. The findings indicate that religious diversity—encompassing Islam, Protestantism, Catholicism, Hinduism, Buddhism, and Confucianism—intersects with ethnic plurality in daily social practices such as communal celebrations, traditional rituals, and economic cooperation. These interactions demonstrate that local culture functions as a practical mechanism for fostering tolerance, mutual respect, national commitment, and non-violence. Despite ongoing challenges related to identity politics and disputes over houses of worship, the article argues that local cultural practices play a mediating role in sustaining interreligious harmony. This study contributes to urban pluralism scholarship by emphasizing diversity as a lived and negotiated process rooted in local cultural dynamics.